Evaluation of total oxidant and antioxidant status in localized and generalized vitiligo. (20th April 2013) - Akoglu, G.; Emre, S.; Metin, A.; Akbas, A.; Yorulmaz, A.; Isikoglu, S.; Sener, S.; Kilinc, F.
Summary Background Vitiligo is an acquired depigmentation disorder, and oxidative stress is suggested to have a major role in its aetiopathogenesis. Aim To assess whether oxidative stress has a greater role in generalized than in localized vitiligo. Methods We assessed 31 patients with active vitiligo (17 localized, 14 generalized) and 38 healthy controls. Serum total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) were determined. Results Patients with vitiligo had significantly lower TAS and higher TOS and OSI values than controls. Both localized and generalized vitiligo were associated with lower TAS and higher TOS and OSI values, compared with controls, and all three did not differ with vitiligo type. Conclusions A systemic oxidative stress exists in patients with vitiligo. These results indicate that the global antioxidant capacity of patients might have been exhausted through a defence mechanism against oxidative processes. The imbalance in TOS/TAS status may have an important role in the aetiopathogenesis of vitiligo, regardless of the clinical variant of the disease.